Increase in blood pressure precedes distress behavior in nursing home residents with dementia. - Kenneth S Boockvar; Tianwen Huan; Kimberly Curyto; Sei Lee; Orna Intrator (PLoS ONE)
Background Distress behaviors in dementia (DBD) likely increase sympathetic nervous system activity. The aim of this study was to examine the associations among DBD, blood pressure (BP), and intensity of antihypertensive treatment, in nursing home (NH) residents with dementia. Methods We identified long-stay Veterans Affairs NH residents with dementia in 2019-20 electronic health data. Each individual with a BP reading and a DBD incident according to a structured behavior note on a calendar day (DBD group) was compared with an individual with a BP reading but without a DBD incident on that same day (comparison group). In each group we calculated daily mean BP from 14 days before to 7 days after the DBD incident day. We then calculated the change in BP between the DBD incident day and, as baseline, the 7-day average of BP 1 week prior, and tested for differences between DBD and comparison groups in a generalized estimating equations multivariate model. Results The DBD and comparison groups consisted of 707 and 2328 individuals, respectively. The DBD group was older (74 vs. 72 y), was more likely to have severe cognitive impairment (13% vs. 8%), and had worse physical function scores (15 vs. 13 on 28-point scale). In the DBD group, mean systolic BP on the DBD incident day was 1.6 mmHg higher than baseline (p < .001), a change that was not observed in the comparison group. After adjusting for covariates, residents in the DBD group, but not the comparison group, had increased likelihood of having systolic BP > = 160 mmHg on DBD incident days (OR 1.02; 95%CI 1.00-1.03). Systolic BP in the DBD group began to rise 7 days before the DBD incident day and this rise persisted 1 week after. There were no significant changes in mean number of antihypertensive medications over this time period in either group. Conclusions NH residents with dementia have higher BP when they experience DBD, and BP rises 7 days before the DBD incident. Clinicians should be aware of these findings when deciding intensity of BP treatment.